What common factors contribute to the leadership of successful inspection outcomes for Early Years Education in English Primary Schools? - Sutton, Richard (2016)
In July 2014, Ofsted reintroduced a separate grading for the provision of Early Years’ education in English primary schools. This dissertation describes research carried out to identify common practices exhibited by headteachers of English primary schools rated at inspection as “outstanding” for their Early Years’ provision. The study looked at all schools in three neighbouring local authorities in the North of England who had received this grading. Data were collected through a survey completed by school leaders, a scrutiny of the schools’ reports and semi-structured interviews with school leaders. Quantitative data from the survey responses were created using a Likert scale. Qualitative data were grouped and compared under the headings of the Ofsted inspection framework. The outcomes show that headteachers of successful schools focus on appointing high quality staff who can effectively lead their setting. They are rarely involved in the day to day provision of education, but ensure a constant high level of expectation. There are wide differences in attitudes concerning the balance between adult and child initiated learning in the outstanding schools. Findings reveal a lack of research into Early Years leadership in schools, and of training opportunities for headteachers in this area.